2024
DOI: 10.3389/fpsyt.2024.1282026
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the Twittersphere: a cross-sectional study of public perceptions, usage patterns, and geographical differences of tweets discussing cocaine

Consuelo Castillo-Toledo,
Oscar Fraile-Martínez,
Carolina Donat-Vargas
et al.

Abstract: IntroductionCocaine abuse represents a major public health concern. The social perception of cocaine has been changing over the decades, a phenomenon closely tied to its patterns of use and abuse. Twitter is a valuable tool to understand the status of drug use and abuse globally. However, no specific studies discussing cocaine have been conducted on this platform.Methods111,508 English and Spanish tweets containing “cocaine” from 2018 to 2022 were analyzed. 550 were manually studied, and the largest subset und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The current data related only to what was anecdotally reported by social media users, whose social, economic, and demographic attributes may not accurately reflect the whole society. Further, as previously highlighted [100], it is also possible that the impact of fake accounts somehow affected our data. Additionally, social media user-related biases may underscore the importance of cautious interpretation and the integration of alternative methodologies in social media studies [101].…”
Section: Discussionmentioning
confidence: 76%
“…The current data related only to what was anecdotally reported by social media users, whose social, economic, and demographic attributes may not accurately reflect the whole society. Further, as previously highlighted [100], it is also possible that the impact of fake accounts somehow affected our data. Additionally, social media user-related biases may underscore the importance of cautious interpretation and the integration of alternative methodologies in social media studies [101].…”
Section: Discussionmentioning
confidence: 76%
“…In another study focusing on opioid-related posts on Twitter, it was also found that healthcare professionals and institutions were the users who generated the most engagement ( 49 ). Similarly, a recent study on societal views regarding cocaine also found that tweets published by healthcare professionals generated the most engagement ( 50 ). Therefore, the fact that in our study both tweets discussing the supposed benefits of smoking and those discussing the health harms of smoking have achieved very similar levels of engagement may be due to the presence of a few accounts classified as undetermined, which have many followers and are promoting the supposed benefits of tobacco.…”
Section: Discussionmentioning
confidence: 86%